Biomarkers of intrahepatic cholangiocarcinoma: diagnosis and response to therapy - Zachary J. Brown; D. Brock Hewitt; Timothy M. Pawlik (Frontiers in Bioscience-Landmark, 2022)
Intrahepatic cholangiocarcinoma (ICC) is the second most common primary liver cancer behind hepatocellular carcinoma (HCC) and carries a dismal prognosis. Improved genetic analysis has paved the way for a better understanding of the distinct somatic genomic landscapes of ICC. The use of next generation sequencing has paved the way for more personalized medicine through identifying unique mutations which may prove to be therapeutic targets. The ability to identify biomarkers specific to ICC will assist in establishing a diagnosis, monitoring response to therapy, as well as assist in identifying novel therapies and personalized medicine. Herein, we discuss potential biomarkers for ICC and how these markers can assist in diagnosis, monitor response to therapy, and potentially identify novel interventions for the treatment of ICC.